Dinâmica do quadro institucional legal para a questão florestal no Brasil nas últimas décadas: uma abordagem a partir da Nova Economia Institucional - Atamanczuk, Mauricio João (2016)
The New Institutional Economics (NIE) is an economic theory that explains the occurrence of development as a result of the institutions that shape the behavior of economic agents. In organizational studies to understand the institutions allows us to understand the limits of behavior of these agents, as well as their performance to the change of the institutional framework. In the forestry perspective, the legal institutions are relevant to determine the behavior of economic agents in various sectors (agriculture, timber, real estate). They ensure that these activities do not generate externalities and environmental problems (global warming, water resource degradation). The formation of the institutional framework on the forest issue is influenced by economic and environmental global context and action of economic agents in the domestic context. Given this context, this thesis aims to analyze aspects that explain how the formal institutional framework contained in the Brazilian legislation on forests was formed and characterized. The overall objective is divided into three specific objectives, each approached on its chapter, conceived as papers, which contain introduction, literature review and its particular methodology. The first specific objective is meant to characterize the forestry externality and ways of solution. presented in two groups of documents: international agreements and event reports about the environment and the Brazilian legislation on forests. The material was treated through the analysis of documents. The second specific objective is analyzing, from the perspective of the New Institutional Economics (NIE), the close relationship between the formation of the institutional / legal framework applied to forestry issues and the speeches of the main reports from the World Conferences on the Environment and international agreements that Brazil has participated. The study was developed from the analysis of documents that establishes a longitudinal comparison between both groups of documents, in order to identify the influence of international documents in the construction of the Brazilian law on forests. The third specific objective is understanding the arguments that legitimize the position of interest groups in the formation of the Brazilian environmental legal framework based on the analysis of two antagonistic fronts’ opinion at the approval of the Federal Law 12,651, of May 26th, 2012, establishing New Brazilian Forest Code. The subject was approached from the discourse analysis and applied the typology of Suchman legitimization strategies (1995) to conduct the analysis. The documents analyzed are of the opinion articles and essays in publications of two acknowledgeable and influential representatives of the interest groups in the debates to constitute the code: environmentalists and farmers. As a result it was found that the forest externalities come from the use of forest resources, land conversion to alternative uses or activities that combine the use of resources with forest conservation. The main features of most forest externalities are the dynamic balance and not monetary profits. Identified settlement mechanisms identified either prevent the alternative land use or encourage the conservation and / or restoration of forests by limiting the possibility of free choice by owner. They are based on regulations and subsidies, mostly. Concerning to the formation of the Brazilian legal framework, it is clear that their content is influenced by international documents. The preservation and sustainable management recommendations limit the possibility of land use for agricultural purposes, or limit to exercise the right of ownership over the rural property. In the national context this aspect generated reaction of interest groups which sought changes in the Forest Code to ensure the free decision on land use, justified by the expansion of the food market. From the analysis of three chapters, it was possible to highlight the relationship between the institutional framework which regulates the use of forest resources to avoid externalities, with the right to property over the land where the forest is located. Although the forest is considered an asset of common interest, the property itself is private (or State) and linked to land ownership. When the right of ownership is associated with the development, it corresponds to the investment interests, but not always conciliatory toward conservation principles. To preserve the forest is necessary to ensure that the limitations on property rights be respected and the incentives may arouse the interest of owners to avoid the negative externalities and / or produce positive externalities.